Recharge of Phreatic Zone/Ground Water through Pervious Concrete (International Journal of Innovative Research in Engineering & Management, 2023)
The pervious concrete framework and its  comparing quality are as critical as its penetrability  characteristics. The quality of the framework not as it  were depending on the compressive quality of the  pervious concrete but moreover on the quality of the soil  underneath it for bolster. Previous studies have shown  that permeable concrete has lower compressive strength  than conventional concrete and can only withstand light  truck loads. This project was an experiment to examine  the compressive strength of permeable concrete as it  relates to the water-cement ratio, aggregate ratio,  aggregate size and degree of compaction. To enhance the  strength and permeability of concrete, it is crucial to  strike a balance between the water-cement ratio and the  presence of voids. By optimizing the proportions of  water, cement, and aggregates, the goal is to minimize  voids without compromising the overall strength of the  concrete. This delicate equilibrium ensures improved  durability and resistance while allowing for adequate  permeability to water and other substances. The aim is to  achieve a cohesive and robust concrete mixture that meets  both structural and functional requirements.. Pervious  concrete pavement is unique and effective means to meet  growing environmental demands, by landing rainwater  and allowing it to seep into the ground.
Keywords: Phreatic zone; Ground water; ervious concrete; aggregate; fly ash; cement; noise barriers; Hydraulic structures; Swimming pool decks; Tennis courts